THE VIEWS OF TEACHERS AND SCHOOL ADMINISTRATORS ON SOCIAL CAPITAL (Third Sector Social Economic Review, 2023)
The aim of this study is to examine the views of teachers and school administrators working in secondary schools in Ankara province on social capital. In this direction, the views of teachers and school administrators working in secondary schools affiliated to the Ministry of National Education on the meaning of social capital, its elements, personal and organizational contributions, the development process in schools, the difficulties encountered and what can be done to develop social capital were examined. The research was carried out with the participants determined by maximum diversity and criterion sampling methods from Çankaya, Yenimahalle, Mamak, Altındağ, Etimesgut, Keçiören and Sincan districts of Ankara province in the 2020-2021 academic year. In this research, which was designed as a case study by adopting qualitative research method, data were collected with a semi-structured interview form. The data obtained were analyzed through descriptive analysis and content analysis. As a result of the research, teachers and school administrators defined social capital as a concept intertwined with cooperation, communication and trust. The participants identified the components of social capital as trust, social networks, participation in activities, school norms and organizational commitment. Teachers and school administrators stated that the existence of social capital positively affected teachers’ sense of belonging to the school, professional motivation and development, academic achievement, and the atmosphere and image of the school. Thus, it was stated that social capital contributes to the efficient functioning of the school. In the development of social capital, it was stated that obstacles such as poor communication between teachers, authoritarian attitude of the school administration, closed communication and passive position of parents in the education process were encountered.
Keywords: Social capital; human capital; economic capital; school administrator; teacher